PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTS. NEGERI LUBUK PAKAM TAHUN PELAJARAN 2015/2016 - Asmalia Asmalia; Mara Samin Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2016)
The problem in this research is that students do not have a high interest to follow the lesson and the students often had difficulty in solving mathematical problems that have an impact on learning outcomes for low math. The purpose of this study in learning is to fix the problems that occurred in the interest and the results of students' mathematics learning. This research is a classroom action research. The experiment was conducted in two cycles, the first cycle and the second cycle, each consisting of 2 meetings and a duration of 2 x 40 minutes. At each cycle consisting of several stages: planning, action, observation, and reflection. From the results of the study in the first cycle, the result of observation that students are said to be good enough to have interest and liveliness in asking when studying mathematics. And also obtained the test results of student learning first cycle with the percentage of classical completeness amounted to 71.05% (27 students) were completed. In the second cycle, obtained an increase from the observation that the students said already good in mathematics and has been very active in student asked the teacher about the lesson of the unknown. And obtained test results II study classical completeness percentage of 89.47% (34 students) were completed, so that the condition of the first cycle after the action on the second cycle increased by 18.42%. The final conclusion is an increase mathematics learning outcomes by implementing cooperative learning model Think Pair Share (TPS).